Recent advances on identification of spermatogonial stem cells and their niche - Gofur, Md Royhan (Asian Journal of Medical and Biological Research, 2020)
Spermatogonial stem cells (SSCs) are the most primitive spermatogonia in the testis. A balance between the self-renewal and differentiation of SSCs, strictly controlled in a special „niche‟ microenvironment in the seminiferous tubules (SSC niche), is essential to maintain normal spermatogenesis. Since the 1950s, many experimental methods, including histology, immunostaining, whole-mount analyses, and pulse-chase labeling, had been used in attempts to identify SSCs. Recent studies demonstrate that Aundiffseem to possess variable levels of stem cell potential to act as SSCs; GFRα1+ population in As has the greatest potential to act as SSCs (can consider as actual SSCs) whereas NGN3+ population in Aundiffhas comparatively much lower potential to act as SSCs (can consider as potential SSCs). The precise identity of SSCs is still being refined. Sertoli cells, directly interact with SSCs, and interstial cells including Leydig cells, testicular macrophages, peritubularmyoid cells and vascular smooth muscle cells, control the proliferation and differentiation of SSCs through the secretion of extrinsic factors, constitute the cellular components of SSC niche which preferentially locates in the region of seminiferous tubules adjacent to the interstitium that always coincide blood vessels. Asian J. Med. Biol. Res. September 2020, 6(3): 375-382